Tumor Immunometabolism Characterization in Ovarian Cancer With Prognostic and Therapeutic Implications - Yang, Miner; Chen, Gaowen; Gao, Kunjie; Wang, Yifeng (Frontiers in Oncology, 2021)
Background: Metabolic dysregulation in the tumor microenvironment has significant impact on immune infiltration and immune responses. However, interaction between immunity and metabolism in ovarian microenvironment still needs further exploration. Methods: In our study, we constructed an immunometabolism gene set and ovarian cancer cohort from TCGA were classified into three immunometabolism subtypes. We explored the relationships between immune infiltration and metabolism reprogramming. Additionally, we built risk score and nomogram as prognostic signatures. Results: Three distinctive immunometabolism subtypes were identified with therapeutic and prognostic implications. Subtype 1, the “immune suppressive-glycan metabolism subtype”, was featured by high levels of immunosuppressive cells infiltration and glycan metabolism activation; Subtype 2, the “immune inflamed-amino acid metabolism subtype”, showed abundant adaptive immune cells infiltration and amino acid metabolism activation; Subtype 3, the “immune desert-endocrine subtype”, was characterized by low immune cells infiltration and upregulation of hormone biosynthesis. Furthermore, we found epinephrine biosynthesis had a significantly negative correlation with MHC molecules, which may result in defective antigen presentation. Conclusion: We proposed immunometabolism subtypes with prognostic implications and provided new perspectives for ovarian cancer microenvironment.